Al-Dirāsāt fi Majāl ‘Ulūm al-Lugah al-‘Arabiyyah wa Ta’līmiha - Muhamad Jaeni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Study of language is very important in the scientific treasure. In fact, many people show less interest in studying linguistic because it is very complex and it requires a deep study in learning it. Generally, the study of linguistics is classified into two parts; they are theoretical linguistics and applied linguistics. Theoretical linguistics has many branches including Phonology, Syntax, Morphology, Stylistic, Semantic, and so forth. Meanwhile the branches of applied linguistics include Psycholinguistics, Sociolinguistics, and the methodology of foreign language learning. The detail information of those studies requires deep and separate study.